Rol de la Gestión humana en el desarrollo de Innovación en organizaciones del sector industrial y educativo en Colombia - Alvarez G., Claudia Milena; Gallego Giraldo, Carmenza; Naranjo H., Christian Guillermo (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
One way of influencing innovation by human talent management is through its contribution to the development of products, processes, services, strategies, the business model or the organization as a whole (Covin & Miles, 1999) , as a support for competitive advantage through the continuous generation and exploitation of new sources of knowledge, which has a significant impact on the financial and market performance of the company (Hayton, 2005). Under this perspective, this paper focuses on determining the role of human management in the generation and development of innovation by Colombian companies. Methodologically, the study was approached from an analytical empirical approach under a type of correlational study for which two types of instruments were designed, on the one hand, a questionnaire and another interview guide. The results contribute, not only the production of useful social and academic knowledge, but also a contribution to the organizations around clarifying new ways in which human management can be the support of innovation. This research work is of great importance as a guide to determine the role of human management in the generation and development of innovation in the companies under study, including the contribution it intends to make for the manufacturing sectors and academia. Among the main results found, it is evident that human management processes do not play a significant role in the generation and development of innovation, since such processes in most of the organizations studied are oriented towards operational processes (Personnel Administration without a strategic sense for the organization and much less for the development of capacities in people), in turn the innovation processes are focused on product-type innovation, neglecting other types of innovation that can generate transformations in practices, strategies and organizational capabilities.